2016
DOI: 10.1152/ajprenal.00208.2016
|View full text |Cite
|
Sign up to set email alerts
|

ASK1: a new therapeutic target for kidney disease

Abstract: Stress-induced activation of p38 MAPK and JNK signaling is a feature of both acute and chronic kidney disease and is associated with disease progression. Inhibitors of p38 MAPK or JNK activation provide protection against inflammation and fibrosis in animal models of kidney disease; however, clinical trials of p38 MAPK and JNK inhibitors in other diseases (rheumatoid arthritis and pulmonary fibrosis) have been disappointing. Apoptosis signal-regulating kinase 1 (ASK1) acts as an upstream regulator for the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…(37) ASK1, a member of the MAPK kinase kinase (MAP3K) family, selectively activates JNK and promotes MKK4/7 phosphorylation. (38) Notably, recent studies have shown that ASK1 is responsive to nutrient apply and closely participated in inflammation, insulin resistance, and hepatic steatosis. Furthermore, using ASK1 binding signals such as TRAF1 may negatively regulate NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…(37) ASK1, a member of the MAPK kinase kinase (MAP3K) family, selectively activates JNK and promotes MKK4/7 phosphorylation. (38) Notably, recent studies have shown that ASK1 is responsive to nutrient apply and closely participated in inflammation, insulin resistance, and hepatic steatosis. Furthermore, using ASK1 binding signals such as TRAF1 may negatively regulate NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IKK and TANK bind to the IRE1/TRAF2 complex and subsequently activate NF-κB signaling. Moreover, ASK1 kinase, a binding partner for TRAF2, exerts several contextdependent effects on inflammation, autophagy, and apoptosis [84]. ASK1 activates the expression of inflammatory genes through the JNK-AP-1 pathway ( Fig.…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
“…Opening of MPTP induces cell death through the release of cytochrome c and subsequent caspase activation [128]. Taken together, these studies identify mitochondria, apoptosis and MAPK and Akt pathways related pathways as potential novel targets for treating trauma-induced AKI [117].…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…This has also been shown in a murine burn model, where topical application of p38 inhibitors reduces epithelial apoptosis and systemic inflammation [115,116]. New upstream targets are being identified that may act on multiple MAPKs for even more pronounced pleiotropic effects [117].…”
Section: Accepted Manuscriptmentioning
confidence: 81%